HUMORAL IMMUNE RESPONSE IN NIGERIANS WITH LONG STANDING TYPE 2 DIABETES MELLITUS - Azenabor, Alfred; Alaba Olagbeni, Olufunmilayo; Oloruntoba Ekun, Ayodele (International Journal of Clinical and Biomedical Research, 2016)
Introduction: Deranged immunologic capability has been widely implicated in diabetic subjects. It is not well documented if dysfunctional humoral antibodies that occur in DM leads to susceptibility to infections as a result of poor glycaemic control or a reaction that occurs when the infection has already set in. We sought to evaluate the pattern of humoral immune response in Nigerians with Diabetic mellitus with and without complications and its association with glycaemic control indices. Methods: This was a cross sectional analytical study conducted on 150 people with type 2 DM between the ages of 38 and 80 years and 75 age and sex matched healthy controls. Presence of co morbidities and complications was sought for in the subjects. DM subjects were subdivided into early onset (less than five years duration) and long standing (greater than five years duration). Glycaemic control was assessed using fasting plasma glucose, fructosamine and glycosylated haemoglobin. Plasma immunoglobulins A, G, and M were estimated using elisa method. Results: The mean levels of all the studied immunoglobulins were comparable in DM and healthy controls save for immunoglobulin M which was significantly lower in DM. A significantly inverse association was observed between immunoglobulin G with fructosamine (r = - 0.356, p = 0.030) and glycosylated haemoglobin (r = -0.352, p = 0.026). Immunoglobulin M was negatively associated with systolic blood pressure (r = - 0.269, p = 0.034 ) and diastolic blood pressure (r = - 0.257, p = 0.044). Conclusion: Plasma levels of Immunoglobulin M are lower in subjects with DM than in people without DM. Plasma Immunoglobulin G and M levels are significantly and inversely associated with glycaemic control indices and blood pressures respectively in DM subjects. KEYWORDS: Diabetes mellitus; Immunoglobulins; Humoral immune response Glycaemic indices.